Exome Sequencing and Genotyping Identify a Rare Variant in NLRP7 Gene Associated With Ulcerative Colitis. (4th December 2017) - Onoufriadis, Alexandros; Stone, Kristina; Katsiamides, Antreas; Amar, Ariella; Omar, Yasmin; de Lange, Katrina M; Taylor, Kirstin; Barrett, Jeffrey C; Pollok, Richard; Hayee, Bu'Hussain; Mansfield, John C; Sanderson, Jeremy D; et al.
Abstract: Background and Aims: Although genome-wide association studies [GWAS] in inflammatory bowel disease [IBD] have identified a large number of common disease susceptibility alleles for both Crohn's disease [CD] and ulcerative colitis [UC], a substantial fraction of IBD heritability remains unexplained, suggesting that rare coding genetic variants may also have a role in pathogenesis. We used high-throughput sequencing in families with multiple cases of IBD, followed by genotyping of cases and controls, to investigate whether rare protein-altering genetic variants are associated with susceptibility to IBD. Methods: Whole-exome sequencing was carried out in 10 families in whom three or more individuals were affected with IBD. A stepwise filtering approach was applied to exome variants, to identify potential causal variants. Follow-up genotyping was performed in 6025 IBD cases [2948 CD; 3077 UC] and 7238 controls. Results: Our exome variant analysis revealed coding variants in the NLRP7 gene that were present in affected individuals in two distinct families. Genotyping of the two variants, p.S361L and p.R801H, in IBD cases and controls showed that the p.S361L variant was significantly associated with an increased risk of ulcerative colitis [odds ratio 4.79, p = 0.0039] and IBD [odds ratio 3.17, p = 0.037]. A combined analysis of both variants showed suggestive association with an increased risk of IBD [odds ratio 2.77, p = 0.018]. Conclusions: The results suggest that NLRP7 signalling and inflammasome formation may be a significant component in the pathogenesis of IBD.